(untitled) (SCAFFOLD: A SHOWCASE OF VANDERBILT FIRST-YEAR WRITING, 2023)
This paper reviews Diane Seuss’s poetry collection: Still Life with Two Dead Peacocks and a Girl. The piece focuses on the thematic development and the poet’s craft evident in the collection. Writing this paper was the first opportunity I have ever been given throughout my academic career to review art. This assignment allowed me to thoroughly analyze a book cover to cover and offer my opinion on the thematic development. Additionally, the book I chose was one of the most complex and creative things I have ever read. Writing this poetry review enabled me to develop my language use and discover how to thoughtfully express my argument. For additional context, watch the author’s reflection on the piece below.